2022
DOI: 10.1186/s12929-022-00815-0
|View full text |Cite|
|
Sign up to set email alerts
|

Long noncoding RNA BCRP3 stimulates VPS34 and autophagy activities to promote protein homeostasis and cell survival

Abstract: Background Autophagy plays important roles in cell homeostasis and protein quality control. Long non-coding RNAs (lncRNAs) have been revealed as an emerging class of autophagy regulators, but the majority of them function in regulating the expression of autophagy-related genes. LncRNAs that directly act on the core autophagic proteins remain to be explored. Methods Immunofluorescence staining and Western blotting were used to evaluate the function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…While initially it was thought that autophagy is solely regulated at the protein level, a seminal report in 1999 showed that gene regulatory changes affect autophagy at a transcriptional level [64]. Moreover, autophagy regulation on the post-transcriptional level by non-coding RNAs has also been described, but less studied [65][66][67]. Although the knowledge on autophagy regulation has been expanded significantly, data on post-translational and (post-)transcriptional regulations are scattered across many resources -making it difficult to find and integrate highquality and relevant data.…”
Section: Discussionmentioning
confidence: 99%
“…While initially it was thought that autophagy is solely regulated at the protein level, a seminal report in 1999 showed that gene regulatory changes affect autophagy at a transcriptional level [64]. Moreover, autophagy regulation on the post-transcriptional level by non-coding RNAs has also been described, but less studied [65][66][67]. Although the knowledge on autophagy regulation has been expanded significantly, data on post-translational and (post-)transcriptional regulations are scattered across many resources -making it difficult to find and integrate highquality and relevant data.…”
Section: Discussionmentioning
confidence: 99%
“…While initially it was thought that autophagy is solely regulated at the protein level, a seminal report in 1999 showed that gene regulatory changes affect autophagy at a transcriptional level [ 65 ]. Moreover, autophagy regulation on the post-transcriptional level by non-coding RNAs has also been described, but less studied [ 66 , 67 ]. Although the knowledge on autophagy regulation has been expanded significantly, data on post-translational and (post-)transcriptional regulations are scattered across many resources – making it difficult to find and integrate high-quality and relevant data.…”
Section: Discussionmentioning
confidence: 99%
“…These cDNA fragments were then subcloned into pRK5 or pLAS5w.PeGFP with a V5 or Flag tag for transient overexpression or packaging lentiviruses carrying Wdr4, respectively. Lentiviruses were generated as previously described [ 24 ]. Wdr4 mutants were generated using site-directed mutagenesis with the following primers: Wdr4 D166A: 5′- TTTGTGCTTACTGCAG C CCGGGATGAGAAGATC-3′ and 5′-GATCTTCTCATCCCGG G CTGCAGTAAGCACAAA-3′, Wdr4 R172Q: 5′-CGGGATGAGAAGATCC A GGTCAGCTGGGCTGCT-3′ and 5′-AGCAGCCCAGCTGACC T GGATCTTCTCATCCCG-3′.…”
Section: Methodsmentioning
confidence: 99%